1985
DOI: 10.1073/pnas.82.8.2306
|View full text |Cite
|
Sign up to set email alerts
|

UGA is read as tryptophan in Mycoplasma capricolum.

Abstract: UGA is a nonsense or termination (opal) codon throughout prokaryotes and eukaryotes. However, mitochondria use not only UGG but also UGA as a tryptophan codon. Here, we show that UGA also codes for tryptophan in Mycoplasma capricolum, a wall-less bacterium having a genome only 20-25% the size of the Escherichia coil genome. This conclusion is based on the following evidence. First, the nucleotide sequence of the S3 and L16 ribosomal protein genes from M. capricolum includes UGA codons in the reading frames; th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
176
0
1

Year Published

1986
1986
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 282 publications
(185 citation statements)
references
References 25 publications
7
176
0
1
Order By: Relevance
“…The expressed protein was a doublet of 72/74 kDa. The DNA sequence of the gene encoding P72 showed that it contained no internal in-frame UGA,,, codons and thus is expressed in E. coli at full length (Yamao et al, 1985). Analysis of the DNA sequence revealed that the P72 gene was preceded by a consensus sequence for a ribosome-binding site.…”
Section: Discussionmentioning
confidence: 99%
“…The expressed protein was a doublet of 72/74 kDa. The DNA sequence of the gene encoding P72 showed that it contained no internal in-frame UGA,,, codons and thus is expressed in E. coli at full length (Yamao et al, 1985). Analysis of the DNA sequence revealed that the P72 gene was preceded by a consensus sequence for a ribosome-binding site.…”
Section: Discussionmentioning
confidence: 99%
“…From the deduced amino acid sequence, the predicted molecular mass of ORFl was 62 kDa. The presence of two UGA codons at amino acid positions 546 and 766 in ORFl precluded the expression of this protein in E. coli (Yamao et al, 1985). Amino acid analysis of the amino terminus of the 28 kDa antigen expressed by PAS1 identified the sequence…”
Section: Dna and Protein Sequence Analysis Of Pas1mentioning
confidence: 99%
“…horninis 7488 reacted with mAb 26.7D (Christiansen et al, 1994). The epitope could be located between the start of the fusion protein (aa 131) and the first UGA codon, which in E. coli codes for stop but in mycoplasmas for tryptophan (aa 371) (Yamao et al, 1985), (Fig. la).…”
Section: Demonstration Of Pi20 In M Horninis Isolatesmentioning
confidence: 99%